Mortality Trends in Crohn's Disease and Ulcerative Colitis: A Population-based Study in Québec, Canada. Issue 2 (February 2016) - Bitton, Alain; Vutcovici, Maria; Sewitch, Maida; Suissa, Samy; Brassard, Paul
Abstract : Background: Mortality rates greater than in the general population have been reported in the population with Crohn's disease (CD), but reports for ulcerative colitis (UC) are conflicting. Trends with time were rarely described. We aimed to assess whether CD and UC mortality in Québec differs from that in the general population and to describe the trends over a 10-year observation period. Methods: This is a population-based cohort study using the Québec administrative health databases and death certificates registry. All-cause and cause-specific standardized mortality ratios (SMRs) were computed for 1999 to 2008. A time trend analysis was used to assess changes in the SMR with the calendar year. Results: All-cause mortality was significantly increased in CD and UC compared to the general population: SMR: CD 1.45 (95% confidence interval: 1.34–1.58), UC 1.21 (95% confidence interval: 1.12–1.32). In CD, mortality from digestive conditions, all neoplasms, digestive neoplasms, and colorectal, lymphatic, and lung cancer was significantly higher than in the general population. In UC, mortality from digestive, respiratory, and infectious conditions was also significantly increased. In both CD and UC, there was a decrease with time in all-cause SMRs and in digestive conditions, digestive neoplasms, colorectal cancer, and infectious diseases. SMRs for lung cancer and respiratory conditions increased over time in CD. Conclusions: All-cause mortality was significantly higher in CD and UC populations than in the general population. However, a decreasing trend with time was observed in all-cause and some cause-specific SMRs. In CD, SMRs for lung cancer and respiratory conditions increased during the observation period. Abstract : Article first published online 11 January 2016